Comprehensive assessment to residents' perceptions to historic urban center in megacity: a case study of Yuexiu District, Guangzhou, China. Issue 5 (3rd September 2021) - Deng, Zhaohua; Chen, Dantong; Qin, Xiaoling; Wang, Shifu
ABSTRACT: Understanding residents' perceptions of the urban form can guide efforts to improve the urban milieu. However, existing research on place perception of historic environment has overlooked the social dimension and focused on isolated historic quarters, resulting in "zones of gentrification." Thus, a comprehensive analytical framework to the urban image inquiry of a megacity historic urban center is proposed to address this gap. An online questionnaire is distributed among the residents of the Yuexiu District in Guangzhou, China. The collected data are processed using ArcGIS to create a 3D cognitive map and a 2D affective map. The relationships between environmental features, subjective evaluated qualities, and residents' perceptions are analyzed statistically where applicable. Results show that large natural features and public spaces are the most prominent for residents of a historic urban center, whereas designated historic districts are rarely noticed. In addition, districts are more imageable than landmarks, paths are frequently overlooked, and contextual sizable forms and functions are highly noticeable, different from conventional studies. Evaluations of walking environments, public spaces, and landscapes and green areas by residents are strongly correlated with their affective experiences. With the above findings, implications in improving socially-oriented urban design strategies in historic urban centers are discussed.